2013
DOI: 10.1007/s00128-013-1008-5
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concentrations in Surficial and Core Sediments from Izmir Bay: An Assessment of Contamination and Comparison Against Sediment Quality Benchmarks

Abstract: The levels of heavy metals were determined in surface and core sediments from the Izmir Bay in 2009. The highest concentrations of As, Cr, Cu, Ni, Pb and Zn were found in the inner bay due to industrial activities. In contrast, maximum levels of Mn, Co, Fe and Al were observed in the outer bay, due to geochemical structure. Cu, Pb, Zn, Ni, As, Cr and Co levels in the upper layer of core sediments were higher than the mean background values of bottom sediments. The enrichment of Cr, Mn, Pb, Zn, Cu and As in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…The typical arsenic concentration of uncontaminated sediment varies between 6 and 100 μg g −1 , with a median concentration of 68 μg g −1 (Ollson 1999). According to Atalar et al (2013), the estimated mean concentration of background As in the Izmir Bay is 21 μg g −1 , which is a local reference value, and the elevated As levels observed in the sediments were attributed to lithogenic sources. The highest concentration found at site 5 was greater than the mean concentration of background As concentration of Izmir Bay.…”
Section: Total Arsenic Concentrationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The typical arsenic concentration of uncontaminated sediment varies between 6 and 100 μg g −1 , with a median concentration of 68 μg g −1 (Ollson 1999). According to Atalar et al (2013), the estimated mean concentration of background As in the Izmir Bay is 21 μg g −1 , which is a local reference value, and the elevated As levels observed in the sediments were attributed to lithogenic sources. The highest concentration found at site 5 was greater than the mean concentration of background As concentration of Izmir Bay.…”
Section: Total Arsenic Concentrationsmentioning
confidence: 99%
“…And, one of these studies on the pollution status of Izmir Bay revealed elevated concentrations of total trace elements (e.g., Ni, Cu, Zn, Cr, Pb, and As) in surface sediments exceeding the threshold effect level (TEL) values implying occasional biological effects (Atalar et al 2013). Arsenic concentrations reported by Atalar et al (2013) were 8-31 μg g −1 , exceeding the TEL of 7.24 μg g −1 . Therefore, the speciation of arsenic in sediments from Izmir Bay is of great significance because it may provide information about the cycling of arsenic in the ecosystem.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Even if presence of anthropogenic pollution in Turkey and even though this had been investigated, the beginning of this pollution or changing of it in geologic time has not been examined methodologically by going through geological layers in ancient times, except for Evans et al (1989) in Marmara, Atalar et al (2013) (Charola et al 2007;Török et al 2007;Gomez-Heras et al 2008;Marszałek et al 2014 Crutzen and Stoermer (2000), Crutzen (2002); Davis (2011) andFisherKowalski et al (2014). As a matter of course, the initiation of the Anthropocene is still unclear and should be discussed for a while in the scientific arena of geology.…”
mentioning
confidence: 99%